Influence of edible coating based on starch and beeswax on the preservation of postharvest quality of Italian tomatoes (Research, Society and Development, 2022)
Tomato (Solanum lycopersicum L.) is one of the main fruits cultivated in the world, with a high content of vitamins and minerals. As it is a climacteric and highly perishable fruit, many losses occur in the post-harvest phase. In this context, the objective of this work was to develop an edible coating to minimize these losses. For this purpose, tomatoes coated with starch (TR1) and with starch and beeswax (TR2) were used. Uncoated tomatoes were used a control (TSR). The effectiveness of the coatings was tested by physical and chemical analysis of the samples (n=8) of each rehearsal (TSR, TR1 E TR2) in storage time of 0, 3, 6, 9 and 12 days: color analysis (a*, b*, L*, C* Hue* and IE), total soluble solids (TSS - ºBrix), total titratable acidity (TTA - %), Ratio (TSS/TTA), pH, firmness (N) and weight loss (g). The results were evaluated by analysis of variance and means comparison by Tukey test (p L*; < C* and < IE*; TSR = < L*; > C*; >IE*), low levels of soluble solids (from 3.75 to 4.35; TSR = 4.92 °Brix max), acidity (from 0.48% to 0.37; TSR = 0.427% max), pH (from 4.50 to 4.42; TSR = 4.48 pH max), greater firmness and lower total mass loss (TR1 = 8.16 g, TR2 = 5.96 g and TSR = 10.12 g) when compared to the uncoated ones. Therefore, the proposed coatings delayed the ripening of tomatoes, prolonging shelf life.